Implementasi Kebijakan Larangan Penggunaan Bahan Peledak dalam Penangkapan Ikan di Kecamatan Tambelan Kabupaten Bintan 2025 - Tenggara Ngabalin; Ardi Putra; Eki Darmawan (CV. Aksara Global Akademia, 2025)
This research investigates the enforcement of explosive fishing prohibitions under Indonesia's Fisheries Law No. 45 of 2009 in Tambelan District, Bintan Regency. The destructive practice of fish bombing, primarily conducted by external fishermen, causes severe marine ecosystem damage, particularly to coral reefs, while reducing local fishermen's catches. Using qualitative descriptive methodology, data were gathered through interviews, observations, and documentation involving law enforcement officials, Fisheries Civil Servant Investigators (PPNS), and fishing communities. The study applies Van Meter and Van Horn's policy implementation framework, analyzing policy objectives and standards, resources, implementing agency characteristics, implementer disposition, inter-organizational communication and coordination, plus social, economic, and political conditions. Results demonstrate suboptimal policy implementation due to resource constraints. Although violations have declined, this reduction does not guarantee future prevention, particularly given Tambelan District's severe infrastructure and facility limitations that hinder comprehensive policy execution. The research recommends strengthening surveillance capacity, conducting regular community outreach programs, and improving cross-sectoral coordination to enhance policy effectiveness and preserve marine resources in Tambelan District.